Hubungan antara Sokongan Sosial dengan Kemurungan dalam Kalangan Penagih Dadah (Jurnal Pembangunan Sosial, 2017)
The study aims to identify the relationship between social supports with depression among drug addicts in Sabah. Two sets of questionnaire were used in this study, the Inventory of Socially Supportive Behaviors (ISSB) questionnaire to measure social support and the Reynolds Adolescence Depression Scale (RADS) questionnaire to measure depression. There were 100 subjects among drug addicts used in this study. Pearson Correlation Analysis showed that there is a significant negative correlation between social supports such as emotional dimensions, information dimensions, adjoining dimension and finally is the dimension of the tool with depression. The finding also revealed that emotional dimension as highest domain of that correlate with depression compares to the others dimensions. The implication of this study suggests that there is a need to develop a holistic and integrated emotional approach on emotional-based modules to support the needs of emotional aspects that affect depression among drug addicts.